Labu Kuning (Cucurbita moschata duchesne) Sebagai Pewarna dan Sumber Β-Karoten pada Mi Jagung Basah - Hafid Bin Lahudi; Ambar Rukmini; Masrukan; Dyah Titin Laswati (AGROTECH : JURNAL ILMIAH TEKNOLOGI PERTANIAN, 2025)
Corn noodles are a gluten-free and high-fiber food product, but contain relatively low levels of β-carotene. To enhance their nutritional value and visual appeal, pumpkin puree (Cucurbita moschata Duchesne), known for its high β-carotene content and natural coloring properties, was added to the formulation. This study aimed to evaluate the effects of pumpkin puree addition on the physical, chemical, and organoleptic characteristics of wet corn noodles. A completely randomized design with one factor was used, comprising four treatment levels: 10%, 20%, 30%, and 40% pumpkin puree based on the total flour weight. The results showed that pumpkin puree significantly increased moisture contents and β-carotene levels (p<0.05), with the highest values found in formulation F4 (40%)—moisture contents of 65.40% and β-carotene of 287.07 µg/100 g (db). However, formulation F3 (30%) demonstrated the most balanced attributes, including bright colour (a = 4.41and b 22.77), optimal texture (cohesiveness 0.21 and adhesiveness 1.89), and the highest overall anelist preference score (overall score 3.0). Therefore, adding 30% pumpkin puree is the optimal formulation for producing wet corn noodles that are nutritious, visually appealing, and well accepted by consumers.